2016
DOI: 10.1186/s12711-016-0186-0
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for dominance to improve genomic evaluations of dairy cows for fertility and milk production traits

Abstract: BackgroundDominance effects may contribute to genetic variation of complex traits in dairy cattle, especially for traits closely related to fitness such as fertility. However, traditional genetic evaluations generally ignore dominance effects and consider additive genetic effects only. Availability of dense single nucleotide polymorphisms (SNPs) panels provides the opportunity to investigate the role of dominance in quantitative variation of complex traits at both the SNP and animal levels. Including dominance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
83
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 33 publications
8
83
1
2
Order By: Relevance
“…If there is directional dominance causing inbreeding depression [29], then inbreeding should be considered in the genetic evaluation models [30]. Otherwise, using pedigree or marker data, estimates of genetic parameters are inflated [30, 31]. In Vitezica et al [22], genomic inbreeding was fitted as a covariate and, in the current study, we prove this reasoning by using a parametric genomic model, such as a GBLUP.…”
Section: Methodsmentioning
confidence: 62%
“…If there is directional dominance causing inbreeding depression [29], then inbreeding should be considered in the genetic evaluation models [30]. Otherwise, using pedigree or marker data, estimates of genetic parameters are inflated [30, 31]. In Vitezica et al [22], genomic inbreeding was fitted as a covariate and, in the current study, we prove this reasoning by using a parametric genomic model, such as a GBLUP.…”
Section: Methodsmentioning
confidence: 62%
“…Using genomic data, Sun, VanRaden, Cole, and O'Connell (2014) reported the ratio of dominance to phenotypic variance for 8 production traits in dairy cattle breeds between 5% and 7%. Aliloo, Pryce, Gonzalez-Recio, Cocks, and Hayes (2016) similarly reported a small dominance variance for milk and fertility traits in Australian Holstein and Jersey dairy cattle. However, Ertl et al (2014) reported a range of low to very high ratio of dominance to total genetic variance for 9 milk production and conformation traits in Fleckvieh cattle and between 3.3% and 50.5% of the total genetic variance.…”
Section: Introductionmentioning
confidence: 92%
“…However, relatively few studies have focused on estimating non-additive genetic effects. Non-additive genetic effects have been ignored due to incomplete pedigrees, computational limitations and requirement of individual phenotypes [i.e., estimated breeding values (EBVs) cannot be used as pseudo-phenotypes] and because selection acts additively (Aliloo, Pryce, González-Recio, Cocks, & Hayes, 2016). Nevertheless, it is suggested that including non-additive genetic effects (epistatic and dominance effects) could improve the accuracy of GS in complex traits (Nazarian & Gezan, 2016;Ober et al, 2015;Sun et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The range of estimated contributions of non-additive genetic variance to total genetic variance differs across studies (Aliloo et al, 2016;Ertl et al, 2014;Fernandez, Legarra, Martinez, Sánchez, & Baselga, 2017;Nishio & Satoh, 2014;Palucci, Schaeffer, Miglior, & Osborne, 2007;Su, Christensen, Ostersen, Henryon, & Lund, 2012;Sun et al, 2014). Inconsistencies may be explained by trait definitions, the size of the data sets used in the analyses, estimation of non-additive genetic relationships between individuals (using pedigree or genomic information), the models used to estimate yield deviations, preselection of genotyped animals, breed and population-specific differences, and confounding effect between additive and dominance variances (Vitezica, Varona, & Legarra, 2013).…”
Section: Introductionmentioning
confidence: 99%